2003
DOI: 10.1021/ja034541a
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylsilylation of Framework Brønsted Acid Sites in Microporous Zeolites and Silico-Aluminophosphates

Abstract: Framework-bound alkoxy groups are well-studied intermediates in zeolite chemistry, but their low stability complicates their spectroscopic study in high-temperature reactions such as alkylation or dealkylation. Taking advantage of the much higher bond strength of Si-O versus C-O, we synthesized trimethylsilylated zeolites by reacting them with phenyltrimethylsilane in a catalytic flow reactor at 648 K. In favorable cases, the reaction accurately titrated the acid sites, and 29Si and 13C MAS NMR spectra of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“… 12–15 The 29 Si NMR chemical shift of trimethylsilyl functionalized zeolites appear at 17 ppm. 63 These results are inconsistent with a silylium character in these materials. To the best of our knowledge, the only [R 3 Si][oxide] type species is i Pr 3 Si + supported on sulfated zirconia ( δ 29 Si = 53 ppm).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“… 12–15 The 29 Si NMR chemical shift of trimethylsilyl functionalized zeolites appear at 17 ppm. 63 These results are inconsistent with a silylium character in these materials. To the best of our knowledge, the only [R 3 Si][oxide] type species is i Pr 3 Si + supported on sulfated zirconia ( δ 29 Si = 53 ppm).…”
Section: Resultsmentioning
confidence: 95%
“…The available 29 Si chemical shi values for R 3 Si-supported on silica and silica-alumina suggested that alkylsilanes do not form R 3 Si + sites. [12][13][14][15]63 This is a result of formation of^SiO-SiR 3 sites on these material surfaces.…”
Section: Formation Of Ion-pairs Withmentioning
confidence: 99%
“…This result can be rationalized by the similarity of C-C and C-O bond energies. Recently, we used the reaction in figure 12(c) to synthesize a thermally stable TMS-derivatized HBeta (*BEA topology) zeolite at 648 K in a flow reactor [33]. In this case, formation of the stronger Si-O bond with clean elimination of benzene resulted in material with reduced acid site density and modified pore characteristics.…”
Section: Inorganic Modification Of the Catalystmentioning
confidence: 99%
“…Post-synthetic modification 120,121 is a method that is employed to reduce the effective channel dimensions of a zeolite, to reduce the number of framework acid sites or to introduce some desired new reactive functionality. Haw and his coworkers recently functionalised the large-pore zeolite H-beta by reaction with trimethylphenylsilane at 648 K, which was found to convert some of the acid sites to their trimethylsilyl derivatives 122 . This work has been extended to a two-step post-synthetic sequence in which HZSM-5 is functionalised with a high selectivity at ambient temperatures.…”
Section: Novel Zeolitesmentioning
confidence: 99%